Incidental Findings Among Youth Participating in Multimodal Imaging Research: Characteristics of Findings and Description of a Management Approach - Roane, Jessica L.; Mio, Megan; Viner, Jacqueline; Bettridge, Ariel; Heyn, Chinthaka; Roifman, Idan; Selkirk, Beth; Kertes, Peter; MacIntosh, Bradley J.; Thayalasuthan, Vivekanandan; Detzler, Garry; Endre, Ruby; et al. (Frontiers in Pediatrics, 2022)
Research imaging in healthy and clinical youth populations yields incidental findings that require a management strategy. Our primary objective was to document the frequency and nature of incidental findings within a research group integrating multiple imaging modalities. A second objective was to describe the evolution of an approach to handling incidental findings. A case example was included to display the intricacies of some of these scenarios. Youth, ages 13-20 years, with bipolar disorder, familial risk for bipolar disorder, or healthy controls, obtained one or a combination of neuroimaging, cardio-thoracic imaging, retinal imaging, and carotid imaging. All images were systematically reviewed for incidental findings. Overall, of 223 participants (n = 102 healthy controls), 59% (n=131) had a brain magnetic resonance imaging (MRI) incidental finding and 27% (n=60) had at least one incidental brain finding requiring non-urgent follow-up. In addition, of 109 participants with chest/cardiac MRI and carotid ultrasound, 3% (n=3) had chest findings, 2% (n=2) had cardiac findings, and 1% (n=1) had a carotid finding. Of 165 youth with retinal imaging, 1% (n= 2) had incidental findings. While the vast majority of these incidental findings were of a non-serious, non-urgent nature, there were noteworthy exceptions. Imaging research groups need a system that emphasizes the value of clinical review of research images and one that is collaborative and responsive, in order to inform follow-up plans. Rating systems that have been developed and used in neuroimaging for the classification of incidental findings can be adapted for use in areas other than the brain. Regardless of severity, incidental findings may raise anxiety in youth participants and their parents. The optimal threshold is one that balances transparency with utility.